“Delapan Puluh, Dua Puluh”: Membangun Budaya Organisasi Dengan Penerapan Prinsip Pareto di KSPPS Bakti Huria Syariah - Andi Amri; Muhammad Nurjaya (Universitas Muslim Maros, 2022)
The 80/20 principle initiated by Vilfredo Federico Damaso Pareto and known as the Pareto Principle. It is a principle in the business world where 20% input will produce 80% output. While a number of literatures shows that there is a significant influence between organizational culture and employee performance, this article focuses on the application of the Pareto Principle in KSPPS Bakti Huria Syariah. This qualitative research was carried out at the KSPPS Bakti Huria Syariah in South Sulawesi Province with two case studies, namely the KSPPS Bakti Huria Syariah Makassar Branch and Maros Branch. While the former represents a branch with many problematic partners/members, the latteris a branch who successfully apply the Pareto Principle. Data was collected using interview and observation. Interviews were conducted with 25 Heads of KSPPS Bakti Huria Syariah Branch and four managers of KSPPS Bakti Huria Syariah Cnetral Office. The study indicates that KSPPS Bakti Huria Syariah has four pillars in the welfare of its members, namely spiritual, economic, educational, and social entrepreneurship which is framed in the Vision